The Development History of Ancient Medical Politics and its Enlightenment to Contemporary Society - Chuhao Zhao, Chenxi Liu (Forest Chemicals Review)
The COVID-19 pandemic has brought Traditional Chinese Medicine (TCM) wide attention again. After more than two thousand years of development, TCM has accumulated rich experience in medical and political management. In order to further promote the development of TCM, spread TCM knowledge and experience, and bring relevant enlightenment to the current medical and political management, we conducted a detailed research and exploration on the history of medical and political development in China over the past 2,000 years by means of literature collection and historical review, and came to the following conclusions: Ancient Chinese TCM talents have formed a perfect selection and assessment system, and it shows the characteristics of the institution setting is becoming more and more complete, the selection of medical officers is healing first, and the inheritance of medical knowledge is especially important. Some suggestions are put forward: the functions of TCM medical administration should be optimized based on classified management; The evaluation of medical talents should take the cure rate as the main standard. The scale of traditional Chinese medicine teacher education needs to be expanded in an orderly manner and private traditional Chinese medicine should be supervised in an inclusive and prudent manner.